2021
DOI: 10.1073/pnas.2020583118
|View full text |Cite
|
Sign up to set email alerts
|

Sea spray aerosol concentration modulated by sea surface temperature

Abstract: Natural aerosols in pristine regions form the baseline used to evaluate the impact of anthropogenic aerosols on climate. Sea spray aerosol (SSA) is a major component of natural aerosols. Despite its importance, the abundance of SSA is poorly constrained. It is generally accepted that wind-driven wave breaking is the principle governing SSA production. This mechanism alone, however, is insufficient to explain the variability of SSA concentration at given wind speed. The role of other parameters, such as sea sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
5
38
2
Order By: Relevance
“…Consequently, the vast majority of the particles of all diameters measured by the OPC showing the diel pattern can be considered dry or slightly humidified sea salt. For particles with D geo larger than about 0.5 μm, previous measurements in the AMBL have also shown that the dominant component of SSA in the marine aerosol mass size distribution is inorganic sea salt 21,22,34,35 , consistent with our findings.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, the vast majority of the particles of all diameters measured by the OPC showing the diel pattern can be considered dry or slightly humidified sea salt. For particles with D geo larger than about 0.5 μm, previous measurements in the AMBL have also shown that the dominant component of SSA in the marine aerosol mass size distribution is inorganic sea salt 21,22,34,35 , consistent with our findings.…”
Section: Resultssupporting
confidence: 92%
“…To this end, given the surface winds range we encountered (U 30 < 16 m s −1 ), as a first approximation, the attribution between the local contribution of N SSA and N LRT can be scaled to the concentration. SSA is produced by the wind stress over the ocean surface, and its concentration has been shown to be (nonlinearly) propositional to the wind speed 4,20,21 , with typical concentrations in the range of 10 s per cubic centimeter 21,22 . Whereas the contribution of N LRT is proportional to the yields of the continental sources (dust, pollution, smoke), the distance the aerosol traveled, and with aerosol lifetime in the atmosphere, in general, inversely proportional to the aerosol size 3,23,24 , the quantity of smaller diameters will be greater.…”
Section: Resultsmentioning
confidence: 99%
“…Wind and waves generate sea spray aerosols [20] that can act as prebiotic chemical reactors [21]. Prebiotic chemistry generated simple amphiphiles (typically with a hydrophilic headgroup and a hydrophilic tail) that provided a surface hydrophobic membrane that enabled evaporation, the concentration of reactants and ion gradients that included proton gradients.…”
Section: The Origin Of Ion Gradientsmentioning
confidence: 99%
“…Wind and waves generate sea spray aerosols [20] that can act as prebiotic chemical reactors [21]. Prebiotic chemistry generated simple amphiphiles (typically with a hydrophilic headgroup and a hydrophilic tail) that provided a surface hydrophobic membrane that enabled evaporation, concentration of reactants and ion gradients that included proton gradients.…”
Section: The Origin Of Ion Gradientsmentioning
confidence: 99%